The investigation of the relationship between throwers' isokinetic strength and throwing speed and distance in the athletics - Aka, H. (International Journal of Applied Exercise Physiology, 2020)
The aim of the study is to investigate the relationship between the isokinetic shoulder strength, the throwing speed and the throwing distance of the medicine ball of the throwers in the athletics. 16 elite athletes voluntarily participated in the study. The eccentric and concentric (60°s-1) shoulder muscle strengths of the participants were determined with an isokinetic dynamometer and the throwing speed was determined with a radar device. Spearman Correlation Analysis was used to determine the relationship between throwers` isokinetic shoulder strength, throwing speed, and medicine ball throwing distances. As a result of the statistical analysis, while a significant relation was not determined between the isokinetic shoulder strength and the throwing speed of the athletes, a positive relation was determined between the shoulder isokinetic strength and the throwing distance of the medicine ball (p <0.05). As a result, although the throwers shoulder muscle strength has a significant effect on the throwing distance of the medicine ball, it has no significant effect on throwing speed. The reason for the significant relationship between shoulder muscle strength and medicine ball throwing distance may be that the throwing motion is applied with the upper limb mostly and the use of other factors in the movement is minimized. The reason for the significant relationship between shoulder muscle strength and medicine ball throwing distance may be that the effect of other factors (technique, rotational speed, explosiveness) has been reduced since throwers` ball throwing distances are determined in a stable position. Therefore, it may be due to the fact that the athlete performs the movement with the upper limb while throwing the medicine ball. On the other hand, the lack of a significant relationship between the shooting speed and shoulder joint strength can be explained by the effect of different variables in the shooting technique (kinetic, kinematic, motoric). Considering this situation, it can be suggested that throwers should develop other variables (strengthening all upper and lower limbs and trunk muscles, throwing technique, etc.) in addition to shoulder strength to improve throwing speed and throwing distances.